Effects of polyoxymethylene dimethyl ether 3 (PODE3) addition and injection pressure on combustion performance and particle size distributions in a diesel engine. (1st January 2021) - Lin, Qinjie; Tay, Kun Lin; Yu, Wenbin; Yang, Wenming; Wang, Zhi
Highlights: Thermal efficiency improves with the usage of P30 at low injection pressure. Increase in injection pressure from medium to high has low impact on PM emissions. Geometric mean diameter of particles decreases with the increase in PODE3 . Addition of PODE3 at medium and high injection pressures lessens PM emissions. P10 shows highest potential in the reduction of soot and ultrafine particles. Abstract: Polyoxymethylene dimethyl ether 3 (PODE3 ) is an up-and-coming renewable fuel. In this study, the effects of PODE3 addition and injection pressure on combustion performance in a diesel engine have been investigated for the first time, with an emphasis on PM emissions in terms of both volume and number concentrations to account for ultrafine particles. Nitrogen oxides have been found to decrease with PODE3 addition at low injection pressure, although an increment has been observed at high injection pressure. The particle size distributions in terms of particle number concentration (PNC) are characterized by a bi-modal distribution, with the higher peak representing accumulation mode particles. At medium and high injection pressures, declines in PNC have been noticed. Furthermore, geometric mean diameter of particles has been found to decrease with the increase in PODE3 due to its additional oxygen content, stronger spray penetration and lack of C–C bonds. Overall, PODE3 has been concluded to be of high potential in terms of soot reduction. Among the diesel/PODE3 blends, although both P30 and P10 exhibit significant soot reductions at 600 bar and 800 bar, P10 is the most promising candidate given its ability to curtail ultrafine particles.